Reconhecimento de padrões em rede social científica: aplicação do algoritmo Naive Bayes para classificação de papers no Mendeley - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia/Universidade Federal do Rio de Janeiro, 2018)
This work is an exploratory research using the Naive Bayes algorithm with the ability to classify documents in Mendeley using the output classes, based on the amount of reading of the documents. Using a series of data that was found during a data collection, a classification is given to check the patterns in the attributes, an end to recognize the social logics of the scientists, that involve both the behavior and its dynamics in scientific social networks. For the purpose of this work, a literature systematic review was applied, with emphasis on the use of methods that involve the use of social networking concepts, as well as the application of a method for the use of algorithms. Created for automatic processing of all data collected at Mendeley.
Keywords: Redes sociais científicas; Mendeley; Lógicas sociais; Naive Bayes; Inteligência artificial; Classificação; Ciência da Informação; Scientific social networks; Social logics; Artificial intelligence; Classification; Information science; Ciência da informação